Penggunaan Media Pembelajaran PhET dalam Setting Cooperative Learning Guna Meningkatkan Penguasaan Materi Gelombang Berjalan - Kalorbobir, Yohana Apriliani Paskalin; Jamaludin, Jamaludin (Pattimura University, 2025)
The research was conducted due to the use of media and learning models that were not varied and ineffective. To overcome this, learning materials specifically on traveling waves were taught using PhET learning media in a cooperative learning setting. This research was quantitative descriptive with a one-group pretest-posttest design. The population in this study was the 11th-grade science class at Angkasa Pattimura High School in Ambon, consisting of two classes. The sampling technique used was purposive sampling with the aim of improving the mastery of the material among students with the lowest scores, where, based on the average scores, the students in class XI IPA-2 had the lowest average scores compared to class XI IPA-1. Thus, the sample used in this study was the students in class XI IPA-2, with a total of 15 students. The instruments used to collect data were tests, namely a pretest and a posttest. Based on the results of the analysis, it can be seen that the use of PhET learning media in a cooperative learning setting can improve students' mastery of traveling wave material. It is hoped that this research can be used as a reference in efforts to help add new insights into the use of PhET learning media in a cooperative learning setting for other materials.